Characterization of risk factors for adjuvant radiotherapy-associated pain in a tri-racial/ethnic breast cancer population. Issue 5 (May 2016) - Lee, Eunkyung; Takita, Cristiane; Wright, Jean L.; Reis, Isildinha M.; Zhao, Wei; Nelson, Omar L.; Hu, Jennifer J.
Abstract : Abstract: Pain related to cancer or treatment is a critical quality of life issue for breast cancer survivors. In a prospective study of 375 patients with breast cancer (enrolled during 2008-2014), we characterized the risk factors for adjuvant radiotherapy (RT)-associated pain. Pain score was assessed at pre-RT and post-RT as the mean of 4 pain severity items (ie, pain at its worst, least, average, and now) from the Brief Pain Inventory with 11-point numeric rating scale (0-10). Pain scores of 4 to 10 were considered clinically relevant pain. The study consists of 58 non-Hispanic whites (15%), 78 black or African Americans (AA; 21%), and 239 Hispanic whites (HW; 64%). Overall, the prevalence of pre-RT, post-RT, and RT-associated clinically relevant pain was 16%, 31% and 20%, respectively. In univariate analysis, AA and HW had significantly higher pre-RT and post-RT pain than non-Hispanic whites. In multivariable logistic regression analysis, pre-RT pain was significantly associated with HW and obesity; post-RT pain was significantly associated with AA, HW, younger age, ≥2 comorbid conditions, above-median hotspot volume receiving >105% prescribed dose, and pre-RT pain score ≥4. Radiotherapy-associated pain was significantly associated with AA (odds ratio [OR] = 3.27; 95% confidence interval [CI] = 1.09-9.82), younger age (OR = 2.44, 95% CI = 1.24-4.79), and 2 or ≥3 comorbid conditions (OR = 3.06, 95% CI = 1.32-7.08; OR = 4.61, 95% CI = 1.49-14.25, respectively). These risk factors may help to guide RT decision-making process, such as hypofractionated RT schedule. Furthermore, effective pain management strategies are needed to improve quality of life in patients with breast cancer with clinically relevant pain. Abstract : Adjuvant radiotherapy–associated acute pain in patients with breast cancer was significantly associated with black or African-American race, age <50 years, and ≥2 comorbid conditions.